Tabu search applied to transmission system expansion planning considering de-planning - Antonio Escobar; Ramón Gallego; Eliana Toro (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
This paper presents two mathematical models and one methodology for the long-term transmission system expansion planning problem considering de-planning. Traditionally this problem is solved searching the lowest cost investment plan for one given period. The elements of the original topology are considered in the solution in traditional planning. If the initial network is unchangeable, the optimization process is undertaken on a constrained space of solutions that can degrade the system performance. The proposed models allow enhancement of the system’s performance by modifying the original topology. The mathematical models are solved using tabu search on two test systems of the specialized literature.